Toward G protein-coupled receptor structure-based drug design using X-ray lasers. (2019) - Ishchenko, Andrii; Stauch, Benjamin; Han, Gye Won; Batyuk, Alexander; Shiriaeva, Anna; Li, Chufeng
No abstract available